Extended Treatment with Apixaban for Venous Thromboembolism Prevention in the Netherlands: Clinical and Economic Effects - de Jong, Lisa A.; Gout-Zwart, Judith J.; Stevanovic, Jelena; Rila, Harrie; Koops, Mike; Huisman, Menno V.; Postma, Maarten J. (TH Open, 2018)
Background Dutch guidelines advise extended anticoagulant treatment with direct oral anticoagulants or vitamin K antagonists for patients with idiopathic venous thromboembolism (VTE) who do not have high bleeding risk.Objectives The aim of this study was to analyze the economic effects of extended treatment of apixaban in the Netherlands, based on an updated and adapted previously published model.Methods We performed a cost-effectiveness analysis simulating a population of 1,000 VTE patients. The base-case analysis compared extended apixaban treatment to no treatment after the first 6 months. Five additional scenarios were conducted to evaluate the effect of different bleeding risks and health care payers' perspective. The primary outcome of the model is the incremental cost-effectiveness ratio (ICER) in costs (€) per quality-adjusted life-year (QALY), with one QALY defined as 1 year in perfect health. To account for any influence of the uncertainties in the model, probabilistic and univariate sensitivity analyses were conducted. The treatment was considered cost-effective with an ICER less than €20,000/QALY, which is the most commonly used willingness-to-pay (WTP) threshold for preventive drugs in the Netherlands.Results The model showed a reduction in recurrent VTE and no increase in major bleeding events for extended treatment in all scenarios. The base-case analysis showed an ICER of €9,653/QALY. The probability of being cost-effective for apixaban in the base-case was 70.0% and 91.4% at a WTP threshold of €20,000/QALY and €50,000/QALY, respectively.Conclusion Extended treatment with apixaban is cost-effective for the prevention of recurrent VTE in Dutch patients.
Keywords: cost-effectiveness; venous thrombosis; apixaban; lifelong treatment; non–vitamin K oral anticoagulants